Characterisation of teaghrelin-like principles from Assam tea cultivated in Thailand. Issue 1 (22nd December 2021) - Li, Yue-Chiun; Tanapichatsakul, Chutima; Pripdeevech, Patcharee; Hwang, Tsong Long; Kuo, Ping-Chung; Tzen, Jason T. C.
Abstract: Teaghrelins were identified as unique acylated flavonoid tetraglycosides and firstly reported in Chin-shin oolong tea. In the present study, two new teaghrelin-like compounds (1 and 2 ) were purified and characterised from Assam tea varieties collected in Thailand. Their chemical structures were constructed by the spectroscopic and spectrometric analysis. These two teaghrelin-like compounds were also not supposed to exhibit significant ghrelin receptor affinity according to the structural comparison with those teaghrelin-like compounds previously reported. In addition, compounds 1 and 2 did not display notable anti-inflammatory activity in human neutrophils assay.